Psychological impact and psychosocial consequences of the COVID 19 pandemicResilience, mental well-being, and the coronavirus pandemic - Ivbijaro, Gabriel (2020)
Since December 2019, the coronavirus (COVID19) outbreak has impacted everyone's daily lives globally, especially those experiencing mental health issues. The well-being and mental healthcare of patients, families, and health-care professionals who have been directly or indirectly affected by this pandemic has not been well addressed. Governments have asked their citizens to take actions, some of which include making sacrifices that may result in dignity violations and moral injury, a term originating in the military to describe the psychological distress that results from actions, or the lack of them, which violate a person's moral or ethical code. Health professionals, individuals, and communities have changed their way of life and working to decrease coronavirus infectivity, causing additional stress and increasing potential for moral injury. It is important to hear the first-hand experience of people affected to understand the new psychosocial stressors that they face in their day to day lives and what they found helpful in managing these. This global survey carried out by the World Dignity Project in collaboration with the Global Mental Health Peer Network is to ensure that the voices of people with lived experience of mental health, their families, and professionals that work with them are heard. Aims: To understand the impact of the coronavirus pandemic on mental health, well-being, and dignity, what has helped and what lessons can be learned to support coping in future. Materials and Methods: Online qualitative and quantitative survey (April 15-June 15, 2020)Participants gave narrative responses to several questions, posting photos or images. Analysis: Narrative responses were analyzed using the Gioia approach, a systematic inductive approach to develop concepts that help make sense of socially constructed worlds. Visual ethnographic data was used to give insight into the participant's socio-cultural context.